"Los ángeles mudos": la renovación poética al servicio de la temática albertiana - Marks, Jeffrey R. (Huarte de San Juan. Filología y Didáctica de la Lengua, 1999)
The reading of "Los ángeles mudos", one of the less studied poems in Alberti’s “Sobre los ángeles”, can provide us with clues that account for the poet's use of a language radically different from his previous works. More than reflecting an aesthetic crisis, this language has a double function: expressing and uniting the poem's two central themes, namely, the impossibility of communication and the consequent division of the lyrical self.
Keywords: Rafael Alberti